Post-Surgical Outcome of Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Two-year postsurgical developmental outcome was assessed in 24 children with infantile spasms treated at the University of California, Los Angeles.